Beyond Seduction: Intimate Apparel as a Tool for Identity Construction and Empowerment Among Gen Z Women - Sephatama Buana Perkasa Ganinda; Royke Hadrian Askari Sembayu; Nadia Septian Kumala Dewi (CV. Era Digital Nusantara, 2025)
This study explores the role of intimate apparel in shaping the identity, sexuality, and self-expression of Generation Z women. Additionally, this study investigates how intimate apparel functions as a tool for empowerment, body positivity, and self-care, in contrast to its traditional perception as a symbol of seduction. Using qualitative ethnographic methods, this study draws data from participant responses and media analysis to examine how personal preferences influence self-confidence, self-esteem, and social perceptions. The analysis in this study is specifically grounded in Michel Foucault’s concept of “technologies of the self” as well as the framework by Jantzen, Østergaard, and Vieira (2006), which positions underwear as a practical instrument for women to autonomously control bodily performance and manage their psychological experiences and identities. Findings mapped through the Quadrant Matrix Diagram indicate that the majority of Gen Z women position themselves in the “Empowerment and Self-Affirmation” quadrant. For this majority group, underwear serves as an extension of identity and internal strength that liberates them from the dominance of the male gaze. Nevertheless, the findings also reveal a dual impact. While underwear holds great potential as a medium for resistance and self-actualization, some Gen Z women still face pressures stemming from cultural obligations, anxiety regarding stigma, and oppressive beauty standards resulting from social media idealization. This study emphasizes the transformative nature of underwear as a medium for self-definition and advocates for a continuous shift in cultural narratives to normalize inclusive representation. By challenging stereotypes, underwear can continue to evolve as an expression of individuality, authenticity, and agency.